A Portuguese translation of the Systemic Clinical Outcome and Routine Evaluation (SCORE): the psychometric properties of the 15‐ and 28‐item versions. Issue 4 (29th September 2017) - Vilaça, Margarida; Relvas, Ana Paula; Stratton, Peter
Abstract: The Systemic Clinical Outcome and Routine Evaluation (SCORE) is one of the most effective evaluation instruments to assess family functioning and to test family therapy results. To determine its applicability in the Portuguese context, we analysed the psychometric characteristics of the short (SCORE‐15) and long (SCORE‐28) versions using a combined sample of 538 Portuguese participants. Results indicate that both versions demonstrate good internal consistency, replicate the original trifactorial solution and significantly differentiate between clinical and community samples. The SCORE‐15 predicted 93.3 per cent of the SCORE‐28 results. Both instruments' reference values and cut‐off points were established. These findings allow us to claim that the current Portuguese translation provides data that are comparable with, and of the same quality as, those obtained using the English language versions. The Portuguese versions can therefore be recommended to measure family functioning in routine clinical practice and research. Practitioner points: SCORE‐15 and 28 are effective in the measurement of the family relationships in general and the family strengths, communication and difficulties in particular They represent sound and useful tools that may be used for research and intervention purposes, both in clinical and community contexts, when a Portuguese version is required The short version is most appropriate for the clinical context due to its conciseness and stronger capacity to predict family functioning